Autoantibodies against muscarinic receptors in breast cancer. Its role in tumor angiogenesis. - Lombardi, Maria Gabriela (2013)
The presence of autoantibodies in cancer has become relevant in recent years. We demonstrated that autoantibodies purified from the sera of breast cancer patients activate muscarinic acetylcholine receptors in tumor cells. Immunoglobulin G (IgG) from breast cancer patients in T1N0Mx stage (tumor size¡Ü2 cm, without lymph node metastasis) mimics the action of the muscarinic agonist carbachol stimulating MCF-7 cell proliferation, migration and invasion. Angiogenesis is a central step in tumor progression because it promotes tumor invasion and metastatic spread. Vascular endothelial growth factor-A (VEGF-A) is the main angiogenic mediator, and its levels have been correlated with poor prognosis in cancer. The aim of the present work was to investigate the effect of T1N0Mx-IgG on the expression of VEGF-A, and the in vivo neovascular response triggered by MCF-7 cells, via muscarinic receptor activation. We demonstrated that T1N0Mx-IgG (10−8 M) and carbachol (10−9 M) increased the constitutive expression of VEGF-A in tumor cells, effect that was reverted by the muscarinic antagonist atropine. We also observed that T1N0Mx-IgG and carbachol enhanced the neovascular response produced by MCF-7 cells in the skin of NUDE mice. The action of IgG or carbachol was reduced in the presence of atropine. In conclusion, T1N0Mx-IgG and carbachol may promote VEGF-A production and neovascularization induced by breast tumor cells via muscarinic receptors activation. These effects may be accelerating breast tumor progression.